2019
DOI: 10.1016/j.heliyon.2019.e02215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of CaCO3/HPC core–shell composite subject to heavy metals adsorption processes

Abstract: Core-shell particles are a class of materials from nanostructures that have received increased attention recently due to their interesting properties and wide range of applications in catalysis, biology, chemistry of materials and sensors. Simple and cost-effective one-pot synthesis route to directly prepare CaCO 3 @highly porous carbon microsphere in a core–shell structure (denoted as CaCO 3 /HPC) had been developed as a high-performance heavy metals sorbent. XRD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…At low initial concentration, all of the Pb 2+ ions were successfully adsorbed (40–100 mg/g) of the adsorbent, proving that indeed at low concentrations the adsorbent is very effective and efficient. Fathy et al. (2019) observed a similar trend when investigating adsorption of Pb 2+ and Co 2+ ions using CaCO 3 /HPC core-shell composite from aqueous solutions.…”
Section: Experimental Results and Analysissupporting
confidence: 61%
See 3 more Smart Citations
“…At low initial concentration, all of the Pb 2+ ions were successfully adsorbed (40–100 mg/g) of the adsorbent, proving that indeed at low concentrations the adsorbent is very effective and efficient. Fathy et al. (2019) observed a similar trend when investigating adsorption of Pb 2+ and Co 2+ ions using CaCO 3 /HPC core-shell composite from aqueous solutions.…”
Section: Experimental Results and Analysissupporting
confidence: 61%
“…Their adsorption process was better modelled using the Langmuir isotherm (R 2 = 0.994). Fathy et al. (2019) investigated the adsorption of Pb 2+ and Co 2+ ions using CaCO 3 /HPC core-shell composite from aqueous solutions and observed that the adsorption process for Pb 2+ ions was better modelled with Langmuir isotherm (R 2 ≥ 0.930) but the adsorption of Co 2+ was better modelled by Freundlich isotherm (R 2 ≥ 0.900).…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The surface of the spheres is covered by a shell of several layers of polyelectrolytes. This system combines the properties of several different components, such as the absorption properties of CaCO 3 microspheres [ 42 ], the photoluminescent properties of AgInS 2 /ZnS QDs, and the magnetic properties of Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%